Application of transgenic zebrafish for investigating inflammatory responses to nanomaterials: Recommendations for new users [version 2; peer review: 2 approved] - Charles R Tyler; Carl Tucker; Adriano G Rossi; Theodore Henry; Lang Tran; Rachel Verdon; Vicki Stone; Helinor J Johnston; Suzanne L J Gillies (F1000Research)
Despite the increasing exploitation of nanomaterials (NMs) in an array of consumer products, there are uncertainties regarding their potential adverse impact on human health. Investigation of whether NMs activate a pro-inflammatory response is routinely used to assess their toxicity in in vitro and in vivo (rodent) studies. The use of zebrafish (Danio rerio) to investigate inflammatory responses to chemicals, pathogens and injury has increased considerably over recent years. Zebrafish have also been used to investigate the role of inflammation in disease pathogenesis and for drug discovery. Availability of transgenic strains which express fluorescent proteins in immune cells (e.g. macrophages and neutrophils) enables the visualization and quantification of immune cell accumulation in the target site(s) of interest. We therefore propose that non protected life stages of transgenic zebrafish have great utility for screening the toxicity of NMs via investigation of inflammatory responses. Indeed, we have successfully used non-protected life stages of transgenic zebrafish with fluorescent neutrophils (TgBAC(mpx:GFP)i114) to investigate inflammatory responses to NMs. The more widespread use of transgenic zebrafish in nanotoxicology could reduce the reliance placed on rodents and thereby promote implementation of the 3Rs principles. As zebrafish continue to grow in popularity it is timely to offer guidance to new users on their use. Here we will reflect on: exposure routes that can adopted  to mimic human/rodent exposure, what transgenic strains and life stages are best suited to investigate inflammatory responses, selection criteria for zebrafish embryos/larvae, the inclusion of appropriate controls, the importance of dose selection and sample size, and how the (inflammatory) response can be quantified. It is hoped that our recommendations will support the development of standard protocols that can be used to assess whether NMs activate inflammatory responses. Importantly, the themes discussed are not restricted to NMs but relevant also to zebrafish application in ecotoxicology or human health focused studies.